Analisis variasi curah hujan harian untuk menentukan ragam osilasi atmosfer di Kota Padang (studi kasus data curah hujan harian tahun 2002-2011) (Analysis of variations in daily rainfall to determine the variety of atmospheric oscillations in the city of Padang (case study of daily rainfall data for 2002-2011)) - Anggia Arista; - Asrul; Sugeng Nugroho (PILLAR OF PHYSICS, 2013)
ABSTRACTThe rain is the important thing in the human life. The higher rainfall can influence the public activities in many life area. They factors that influence rainfall are geographic position in a region and atmosphere phenomenon. Many atmosphere oscillation phenomenons are MJO, SAO, AO, QBO and ENSO. By knowing the phenomenon or oscillation of atmosphere are happened in a region can give the benefits for the human. Because of that the writer interested to do a researche about Analisys of Rainfall’s Daily Varian to Determine Atmosphere Oscillation Variation in Padang by using detailed result of rainfall in Padang on periode 2002-2011. This researche is a descriptive researche the data are used in this researche is the detailed result of daily rainfall in Padang from BMKG Tabing that have been taken from 2002 to 2011. The determination of rainfall’s variation can be proceed by using exel program and determination of oscillation manner can be determinate by using WWZ program an serfer 7. Based on analisys of rainfall’s data are gotten that highest rainfall’s happened in March and September while oscillation manner are gotten that they are oscillation of daily atmosphere or MJO, seasonal oscillation (SAO), annual oscillation (AO) and quasi biennial oscillation (QBO). Dominant oscillation manner was happened in Padang is the atmosphere oscillation type MJO that 25 times happen in range of time 2002-2011. Keywords:  Rain, oscillation, phenomenons of atmosphere